Upaya Pengolahan Dan Pemanfaatan Air Limbah Domestik Pada Industri AMDK Dan Beverages: Upaya Pengolahan dan Pemanfaatan Air Limbah Domestik Industri AMDK dan Beverages di Jawa Timur - Zevhianan, Acbellita Ayu (Universitas Bojonegoro, 2023)
Industrial wastewater consists of produced wastewater and domestic wastewater. Industrial domestic wastewater comes from the sanitation activities of workers and supporting facilities such as canteens, mosques, and prayer rooms that must be treated so as not to pollute the environment. The industry in the case study engaged in the Bottled Drinking Water (AMDK) and Beverages Industry has tried to treat and even utilize 100% of its domestic wastewater. Processing is carried out through the Sewage Treatment Plant (STP) facility with a biological process capable of removing BOD; COD; TSS; Oils & Fats; Ammonia; Total Coliform; Fecal Coliform; and Residual Chlorine parameters by 95%; 98%; 36%; 95%; 99%; 97,8%; 97,8; and 99% and has been below the quality standard. The percentage of pH and TSS removal is quite low because the influent measurement is still below the quality standard, so processing is focused on lowering organic parameters which are quite high. After treatment, wastewater is reused 100% for watering and washing. Domestic wastewater utilization of AMDK and Beverages Industry can reduce the use of clean water for RTH watering by up to 74%, and the rest is used for hydrants and sprinkler reservoirs.